Backwards integration and strategic delegation - Matthias Hunold; Lars-Hendrik Röller; Konrad Stahl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We analyze the effects of downstream firms' acquisition of pure cash flow rights in an efficient upstream supplier when all firms compete in prices. With an acquisition, downstream firms internalize the effects of their actions on their rivals' sales. Double marginalization is enhanced. Whereas full vertical integration would lead to decreasing, passive backwards ownership leads to increasing downstream prices and is more profitable, as long as competition is sufficiently intensive. Downstream acquirers strategically abstain from vertical control, inducing the efficient supplier to commit to high prices. All results are sustained when upstream suppliers are allowed to charge two part tariffs.
Keywords: L22; L40; 330; double marginalization; strategic delegation; vertical integration; partial ownership; common agency; Lieferanten-Kunden-Beziehung; Vertikale Konzentration; Kapitalbeteiligung; Übernahme; Prinzipal-Agent-Theorie; Betriebliche Preispolitik; Preiswettbewerb; Wettbewerbsbeschränkung; Theorie